Application of a targeted amplicon sequencing panel to screen for insecticide resistance mutations in Anopheles darlingi populations from Brazil - Holly Acford-Palmer; Alice O. Andrade; Jody E. Phelan; Rosa A. Santana; Stefanie C. P. Lopes; Jansen F. Medeiros; Taane G. Clark; Maisa S. Araujo; Susana Campino (Scientific Reports)
Abstract Large-scale surveillance and informed vector control approaches are urgently needed to ensure that national malaria programs remain effective in reducing transmission and, ultimately, achieving malaria elimination targets. In South America, Anopheles darlingi is the primary malaria vector and is responsible for the majority of Plasmodium species transmission. However, little is known about the molecular markers associated with insecticide resistance in this species. In this study, we developed a low-cost, high throughput amplicon sequencing (“amp-seq”) panel, consisting of 11 amplicons targeting genes linked to mosquito species identification (cox-1 and its2) and insecticide resistance (ace-1, GSTe2, vgsc and rdl). When used in tandem with dual-index barcoding of amplicons, this approach permits high numbers of loci and samples to be sequenced in single runs, thereby decreasing costs and increasing efficiency. By screening 200 An. darlingi mosquitoes collected in Brazil, our amp-seq approach identified 10 point mutations leading to amino acid changes in ace-1 (V243I, N294H, S673N, S674N/T) and GSTe2 genes (I114V, D128E, T166I, T179I, and T205A). Overall, our work has demonstrated the utility of amp-seq to provide insights into the genetic diversity of An. darlingi mosquitoes. The amp-seq approach can be applied as a wide-scale insecticide-resistance surveillance technique to better inform vector-control methods.